POLA PENDEWASAAN GEREJA KRISTEN JAWA (GKJ) STUDI KASUS: PEPANTHAN TOHUDAN - Hari Santoso (JURNAL PENABIBLOS, 2019)
Maturity (Breeding) Research on Javanese Christian Church (GKJ), Case Study: Pepanthan Tohudan aims to explain the supporting factors for the maturity (breeding) of Tohudan pepanthan, explain the strength aspects of the supporting factors feasibility, explain the efforts to increase the strength aspects of feasibility, explain the models or patterns the maturation (breeding) of the Tohudan pepanthan church. The focus of the study, entitled The Maturity Pattern of the Javanese Christian Church (GKJ) The Case Study of Tohudan Pepanthan is the feasibility of the Tohudan pepanthan church to become an independent or mature church, breeding from GKJ Manahan. This research was conducted at GKJ Manahan pepanthan Tohudan with qualitative research methods with domain and taxonomic analysis as Spradly's model. Based on domain analysis, it was found that there were nine domains of maturity (breeding) of the Tohudan pepanthan church. Taxonomic analysis of adult church attributes in the Tohudan pepanthan was found to be feasible in the leadership aspects and implementation of the church's vocation duties.